Gender equity in vision care seeking behavior among caregivers: evidence from a randomized controlled trial in rural China - Huan Wang; Claire Cousineau; Yingjie Fan; Sarah-Eve Dill; Matthew Boswell; Scott Rozelle; Xiaochen Ma (BMC, 2022)
Abstract Background Despite rising incomes and rapid economic growth, there remains a significant gender gap in health outcomes among rural children in China. This study examines whether the gender gap in child health is related to the behavior of caregivers when seeking healthcare, and whether healthcare subsidies help to bridge the gender gap in rural health outcomes. Methods Focusing on vision care specifically, we draw on data from a randomized controlled trial of 13,100 children in Gansu and Shaanxi provinces in China that provided subsidized eyeglasses to myopic children in one set of schools (henceforth, referred to as the treatment schools) and provided prescription information but not subsidized eyeglasses to myopic children in another set of schools (control schools). Results The baseline results reveal that while female students generally have worse vision than male students, they are significantly less likely than male students to be taken by their caregivers to a vision exam. The experimental results indicate, however, that caregivers respond positively to both health information and subsidized healthcare, regardless of the gender of their children. When prescription information is paired with a subsidy voucher for healthcare (a free pair of eyeglasses), the uptake rate rises dramatically. Conclusions The gender gap in healthcare can be minimized by implementing subsidized healthcare policies. Trial registration The protocol for this study was approved in full by Institutional Review Boards at Stanford University (Palo Alto, California, USA) and the Zhongshan Ophthalmic Center of Sun Yat-sen University (ZOC, Guangzhou, China). Permission was received from local Boards of Education in each region and from the principals of all schools. The principles of the Declaration of Helsinki were followed throughout. The original trial (Registration site: http://isrctn.org . Registration number: ISRCTN03252665 ) was designed to study the effect of providing free spectacles on children's educational performance. The original trial was retrospectively registered on 09/25/2012.